2014
DOI: 10.1097/gox.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

A Toe Keloid after Syndactyly Release Treated with Surgical Excision and Intralesional Steroid Injection

Abstract: Summary:A keloid is a benign fibroproliferative disease of unknown etiology. Although it is common among Asians, the development of keloid on the foot is rare. We experienced a case of a keloid which arose on the foot of a 4-year-old boy after the surgical release of syndactyly. He had congenital cutaneous syndactyly of the third and fourth toes. After the reconstructive operation was performed when the patient was 2 years old, the wound became hypertrophic and grew to 37 × 37 × 8 mm. After the diagnosis of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…The surgery often involved total excision followed by skin grafting. 1 , 2 , 9 None employed core excision. In core excision, only the fibrous mass of the keloid is removed; the tissues on top are partly spared and serve as flaps to close the defect after excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgery often involved total excision followed by skin grafting. 1 , 2 , 9 None employed core excision. In core excision, only the fibrous mass of the keloid is removed; the tissues on top are partly spared and serve as flaps to close the defect after excision.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the previous case reports on toe keloids, surgery was combined with postoperative compression therapy, 4 steroid injections, 2 , 5 , 7 or methotrexate treatment. 9 However, in a recent case, Liu et al 8 reported removing two big-toe keloids from a patient via total excision followed by skin-flap transplantation, after which the toes were irradiated to prevent recurrence and subjected to hyperbaric-oxygen therapy to prevent any blood flow disorders in the flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keloid formation on the toes and fingers is rare, and thus far, only 22 cases in 9 studies have been reported. [ 7 15 ] Keloid formation after nail extraction is also quite rare. No previous report has identified a keloid caused by nail extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Keloids are rare on digits and only 23 cases have been reported in 10 studies, with most of them appearing following syndactyly treatment. 5 There have been no reports on keloid formation after congenital form of Boutonniere deformity. There is no consistent standard treatment available for keloids formed in the toes and fingers.…”
Section: Figmentioning
confidence: 99%